Introduction - Ludovico Franco (Quaderni di Linguistica e Studi Orientali, 2020)
It is a great pleasure to introduce readers to this special issue of Quaderni di Linguistica e Studi Orientali (Working Papers in Linguistics and Oriental Studies), focusing on the morpho-syntax of (Romance based) Creole and Mixed languages. The papers in this volume address this issue from a variety of viewpoints. It is our humble hope that we have succeeded in broadly enriching the perspective on language creation, contact and change by speaking across different theoretical frameworks and diff erent sets of data.